2016
DOI: 10.1158/0008-5472.can-16-0022
|View full text |Cite
|
Sign up to set email alerts
|

Stromal-Based Signatures for the Classification of Gastric Cancer

Abstract: Treatment of metastatic gastric cancer typically involves chemotherapy and monoclonal antibodies targeting HER2 (ERBB2) and VEGFR2 (KDR). However, reliable methods to identify patients who would benefit most from a combination of treatment modalities targeting the tumor stroma, including new immunotherapy approaches, are still lacking. Therefore, we integrated a mouse model of stromal activation and gastric cancer genomic information to identify gene expression signatures that may inform treatment strategies. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Fifth, both classifications insist on epithelial cells, but none of them take into account the active, nonmalignant stromal cells. Actually, not only gene expression profiles deriving from stromal tissues may influence assignment to a specific molecular category, thus creating interpretative troubles[8], but also novel stromal-based distinctive signatures have been proposed and related to the predominant cancer phenotype[9]. …”
Section: The Importance and Limitations Of Molecular Classificationsmentioning
confidence: 99%
“…Fifth, both classifications insist on epithelial cells, but none of them take into account the active, nonmalignant stromal cells. Actually, not only gene expression profiles deriving from stromal tissues may influence assignment to a specific molecular category, thus creating interpretative troubles[8], but also novel stromal-based distinctive signatures have been proposed and related to the predominant cancer phenotype[9]. …”
Section: The Importance and Limitations Of Molecular Classificationsmentioning
confidence: 99%
“…A deeper understanding of the complexity of the tumor milieu and the molecular and cellular dynamics of tumor angiogenesis will be necessary to predict the clinical responsiveness of individual cancers. For the future, predictive angiogenic biomarkers will be indispensable tools for rational treatment allocation and cost containment [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, multiple studies in GC have established the association of stromal content with survival outcomes and/or therapeutic responses. [73][74][75][76][77][78][79] Notably, high stromal gene expression consistently predicted poor clinical outcome in several independent GC cohorts, 73,77 which could, in part, explain the poor clinical prognosis of Lauren's DGC subtype which is typically characterized by high stromal infiltration and close interaction between cancer cells and CAF. 80 Digging deeper into the complex interactions and cross-talk between cancer cells and their associated microenvironment therefore holds the potential to reveal actionable targets in this devastating subtype.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…This was clearly exemplified by Isella et al where the mesenchymal transcriptional subtype of CRC was found to be predominantly driven by stromal components, suggesting a possible superimposition of the EMT process in tumor cells with the inherent mesenchymal traits of stromal cells. In this regard, multiple studies in GC have established the association of stromal content with survival outcomes and/or therapeutic responses . Notably, high stromal gene expression consistently predicted poor clinical outcome in several independent GC cohorts, which could, in part, explain the poor clinical prognosis of Lauren's DGC subtype which is typically characterized by high stromal infiltration and close interaction between cancer cells and CAF .…”
Section: Confounding Layers Of Complexities Underlie Gc Classificationmentioning
confidence: 99%